DEVELOPMENT OF E-MODULE WITH PROBLEM-BASED LEARNING MODEL ON HUMAN DIGESTIVE SYSTEM MATERIALS AT SMPN CITY OF BENGKULU - Sri Widia Astuti; Sukarno Sukarno; Meirita Sari (Universitas Bhinneka PGRI, 2024)
This research is a type of ADDIE model development research aimed at developing e-modules based on problem-based learning models. The percentage of achievement of the feasibility analysis results is 80.6% for material experts, 97.3% for linguists, and 95% for media/design experts that the product is suitable for use. The response results showed